2007
DOI: 10.1111/j.1447-0756.2007.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide metabolite levels in preterm labor

Abstract: Higher nitric oxide metabolites in women with preterm labor are marker of subclinical infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…In this context, the combination of these 3 factors to create a prediction model for PTD gives appreciable meaning to the present study, as demonstrated by the diagnostic accuracy of the model. Both the current study and previously published studies [15,21] excluded women with signs of chorioamnionitis; however, on multivariate analysis, the presence of genital infection was not associated with PTD. The published data on the role of infection in PTL seem to be inconsistent.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…In this context, the combination of these 3 factors to create a prediction model for PTD gives appreciable meaning to the present study, as demonstrated by the diagnostic accuracy of the model. Both the current study and previously published studies [15,21] excluded women with signs of chorioamnionitis; however, on multivariate analysis, the presence of genital infection was not associated with PTD. The published data on the role of infection in PTL seem to be inconsistent.…”
Section: Discussioncontrasting
confidence: 64%
“…Many studies have shown that decreased levels of cervical NOx are associated with post-term pregnancy [16], whereas elevated levels of cervical, plasma, and urinary NOx are associated with PTL [15,[18][19][20]. However, to date, only 1 study has assessed the potential value of vaginal NOx level as a predictive factor for PTD-with elevated vaginal NOx levels associated with preterm birth [10].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Inflammation induces the up-regulation of ROS and can cause overt OS, resulting in tissue injury and subsequent preterm labor [249]. The concentration of Mn-SOD increases as a protective response to inflammation and OS, and down-regulates NF-kappa B, activator protein-1, and MAPK pathways [250].…”
Section: Pregnancy Complicationsmentioning
confidence: 99%